An FTIR Study of Characterization of Neat and UV Stabilized Nylon 6,6 Polymer Films - Mahdi, H. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The work is concerned with the characterization of as cast films of neat and UV-stabilized nylon 6,6 by employing FTIR measurements. Band assignment is made for neat and UVstabilized nylon 6,6 using FTIR spectra confirm their molecular structure. UV-stabilizer added to nylon 6,6 has caused reduction in the absorbance of the vibrational bands and thus stabilizes the behavior of the polymer in the end and uses specially in harsh environment.